COMPUTER SIMULATION OF RADIATION DEFECTS IN CARBON NANOSTRUCTURE OF GRAPHEN - Ilyin, A.M.; Nemkaeva, R.R.; Ospanova, M.U.; Kim, M.I.; Dokuchaeva, O.G. (Recent Contributions to Physics, 2008)
This work contains results of computer experiments by simulation and investigation of radiation defects in carbon nanostructure of graphen. The calculations of structure relaxation in vacancy zone were carried out by quantum-chemical methods; the relaxation’s influences on defect’s energetic were estimated. Stable configuration of three- dimensional defect arising during adsorption of knocked atom by graphite plane was found. Bond energy of this defect was defined.